Symposium 3: The Metaphor of Patchworking as a Viable Concept in Developing Networked Learning? - Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2008)
The aim of this paper is to explore the notion of networked learning and to further develop the theoretical and methodological concepts within this area of research. It does so through introducing the metaphor of patchworking as a way of understanding and investigating learning processes and by discussing how this particular perspective might inform networked learning. The metaphor has emerged from a detailed interactional study of a short, intensive learning process in which eight young people (age 13-16) worked collaboratively with an open-ended problem. Throughout the process the learners were co-located, but their work was heavily mediated by and dependent on ICT in the form of e.g. tablet-PC's, video-cameras, mini-discs, internet access and the use of various software applications. Furthermore, the learners were put in contact with 'experts' and other resource persons, whom they could interview and discuss with - also they were given a 30 minutes lecture by local researchers. The notion of metaphorically understanding learning as a process of patchworking encompasses for one thing a particular view of learning, but also it suggests specific ways of analytically approaching learning processes. It suggests that we can metaphorically view learning as processes of creating or stitching a patchwork by assembling and continuously reorganising multiple patches and pieces into a 'final' patchwork. Furthermore, it suggests that it is not the 'final patchwork' in and of itself, which should be the object of analysis. Rather, the analytic focus is to investigate how, when and why various 'patches and pieces' (or resources) such as ideas, arguments, pictures or web-texts are stitched together into provisional patchworks, which are combined, reorganised, negotiated and assembled into a 'final' patchwork. In the paper some of the analytic concepts, methods and theoretical ideas will be discussed in relation to a particular interpretation of networked learning. The discussion will revolve around the view of learning in networked learning and how networked learning provides another perspective than other ideas and fields. Also, the paper will discuss the nature of the case, as the case is different from what is often the object of study within the area of networked learning. In spite of this the paper will argue that the insights gained from the study can feed into and contribute to theory and methodology within the area of networked learning. An important concept in the particular interpretation of 'networked learning' discussed in the paper is the notion of promoting connections - both between learners, between learners and teachers, but also connecting people with 'resources'. This paper argues that the learning is not only located in the 'connections' or 'interactions' between the entities. Rather, it is located in a flow of activities, and the paper argues that the metaphor of understanding learning as a process of patchworking can enhance the analytic focus of network learning. An important part of metaphorically understanding learning as a process of patchworking, is the analytic focus on studying flows of activities and closely inspecting how connections to other people and resources come to shape and form the learning process and the construction of knowledge.